Innovations in Patient Respiratory Care Services: A Systematic Review of Emerging Technologies in Intubation and Mechanical Ventilation Outcomes - Mohammed Abdu Rajhi, Bader Mashan Almutairi, Fatimah Ahmed Khormi, Fatim Mohammed Masmali, Amal Ali Najmi; Ameera Hamoud Zoqail, Sarah Abdullah Alamoudi, Yaqoub Abdullah Daghas, Sarah Hassan Maqbul, Sharifah Ahmed Khormi (Journal of International Crisis and Risk Communication Research, 2024)
Background: Patients with acute respiratory failure require mechanical ventilation (MV), an important critical lifesaving intervention. Invasive and non-invasive respiratory support (NIRS) devices have seen recent innovations and have aimed to improve patient outcomes and reduce complication. Recent interest has emerged in non-invasive methods, like high flow nasal cannula (HFNC) and non-invasive positive pressure ventilation (NIPPV) that can reduce intubation and hasten recovery. Aim: The aim of this systematic review was to assess the effectiveness of mechanical ventilation and NIRS on patient outcomes, mortality and complications in both high resource settings and resource limited settings. Method: Studies published between 2020 and 2024 were searched systematically in MEDLINE, EMBASE, and the Cochrane databases. Randomized controlled trials, cohort studies, and meta-analyses of MV and NIRS devices in critical care settings were included. Results: Significant improvements in non-invasive respiratory support devices were also found, especially as a means to reduce intubation rate and improve patient outcome in the ICU as well as in general ward settings. Both of these interventions were effective in both high resource and resource limited environments, but limitations were seen in certain patient populations. Conclusion:New ways of mechanical ventilation and non-invasive support have had a substantial impact on patient care, providing viable alternative to invasive modalities. Still further studies will be necessary to refine these technologies and to develop a framework for their appropriate use in varied clinical settings.